Manejo da irrigação no feijoeiro, cultivado em semeadura direta e convencional - Carvalho, José Joaquim; Saad, João Carlos Cury [UNESP]; Cunha, Fernando Nobre; Silva, Nelmício Furtado da; Teixeira, Marconi Batista (INOVAGRI, 2014)
Brazil is the largest producer and consumer of common bean Phaseolus vulgaris L is currently the most cultivated in the world. Before mainly grown by family farmers, but the bean has been cultivated by farmers who have the most varied levels of technology, increase in productivity. The drought and excess water or soil, causes a direct effect on grain yield and in this sense it is observed that plant growth is a physiological process most sensitive to water deficit, so irrigation has a positive influence on plant productivity from that associated with the proper management of the same. In general, Sao Paulo state presents defined periods of dry and rainy seasons. During rainy season, rainfall distribution is irregular, decreasing the bean yield when the dry period coincides with the crop critical water stage. The objective of the study was to evaluate three irrigation scheduling methods: tensiometer, Class A Pan evaporation, and evapotranspiration estimated by Penman-Monteith equation, all of them combined with two soil management conditions: conventional and no-tillage. The bean sowing was accomplished on 09/29/2008 using cultivate BRS Pontal. Previously this experiment, black oats culture was cultivated in an area which was fallow for three years. The results showed that there was differences among irrigation scheduling methods in the conventional soil management and all treatments in this study showed significantly higher yields than the non-irrigated treatment. In the conventional soil management all irrigation scheduling methods provided larger applied water efficiency compared to no-tillage.

O Brasil é o maior produtor e consumidor de feijão comum Phaseolus vulgaris L cultivado por décadas principalmente pela agricultura familiar e, atualmente cultivado por produtores rurais com elevado níveis tecnológicos, no incremento da produtividade. O déficit hídrico e ou excesso de água no solo, ocasiona efeito direto no rendimento de grãos; nesse sentido observa-se que o crescimento das plantas é um dos processos fisiológicos mais sensíveis ao déficit hídrico, assim a irrigação exerce influência positiva na produtividade vegetal, desde que associado ao adequado manejo da mesma. O Estado de São Paulo, de maneira geral, apresenta períodos secos e chuvosos bem definidos. O presente trabalho teve por objetivo avaliar três métodos de manejo de irrigação: por tensiometria, tanque classe A, e pela evapotranspiração estimada pela equação de Penman-Monteith, todos aplicados em dois manejos de solo: plantio direto e convencional. A semeadura da cultivar BRS Pontal foi realizada em 29/09/2008, em sucessão ao cultivo de aveia preta numa área que estava em repouso há três anos. Avaliaram-se a produtividade de grãos, número de vagens por planta, número de grãos por vagem, massa de 1000 grãos, Número de vagens chochas, lâmina total e eficiência de uso da água. Os resultados do manejo da irrigação baseado no tanque Classe A e o de Penman-Monteith apresentaram uma lâmina média aplicada maior que o do tensiômetro.
Management of irrigation in bean grown in direct seeding and conventional
Keywords: Productivity; Irrigation; Comparison of methods; Phaseolus vulgaris; Soil management; Produtividade; Irrigação; Comparação de métodos; Phaseolus vulgaris L; Manejo do solo